Effect of Annealing temperature on the Structural, Optical and Sensitivity Properties of Nanostructure SnO2 Films to CO2 and NH3 Gas - Yousif, Ali; khudadad, Ameer (Iraqi Journal of Science, 2023)
In this research, we studied the structural properties of SnO2 films nanostructure which prepared by chemical spray pyrolysis method at room temperature on the rules of glass heated (400oC) with rate of spraying (2.5 ml/ min). The effect of annealing temperaturs (450,500,550,600 and 650oC) for two hours on those properties has been indicated. The results of x-ray diffraction showed that all of the prepared films were polycrystalline with tetragonal type and orientation was (110) for all models before and after annealing, and the annealing led to an increase in the grain size. The full width at half maximum (FWHM) values of the (110) peaks of the films decreased from 1.492o to 1.064o with increasing annealing temperature .The surface morphology of the (SnO2) nanostructure films have been studied using atomic force microscopy (AFM) which indicated that the grown films showed good crystalline and homogeneous surface . The Root Mean Square (RMS) values and surface roughness of the films decreased with increasing the annealing temperature. The optical properties of the films were studied by (UV-VIS-NIR) spectrophotometer in the wavelength range (300-1100 nm). The optical transmission results showed high transmittance (87%) at annealing a temperature (650oC). The energy gap for direct transmission was calculated before and after annealing. From the gas sensing measurements of SnO2 films for (CO2 , NH3), showed a good sensitivity at 50oC. It was found the that best sensitivity of SnO2 films at annealing temperature 650oC were (100%) for NH3 (98.78%).